SISTEM INFORMASI GEOGRAFIS BERBASIS WEB SEBARAN LOKASI FASILITAS KESEHATAN DI KOTA TOMOHON - Alfivania Dehelena Posumah; John Socrates Kekenusa; Winsy Christo Deilan Weku (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
Technological developments are currently developing very rapidly, has even become a basic need of society in the modern era of globalization. GIS technology is an assistive technology that can represent the real world on a computer monitor. This research aims to create a web-based that contains information about the location distribution of health facilities in Tomohon City. Based on the waterfall design method and using the Google Maps API in determining the coordinates of existing health facilities using the latitude and longitude of these tourist attractions for WebGIS creation, it shows that using the maps feature in WebGIS can make it easier for people to find out the location of hospitals and health centers.